Frequency and Neural Correlates of Pauses in Patients with Formal Thought Disorder - Matsumoto, Kazunori; Kircher, TIlo; Stokes, Paul; Brammer, Mickael J.; LIddle, Peter; McGuire, Philip K. (Frontiers in Psychiatry, 2013)
Background: Pauses during speech may reflect the planning and monitoring of discourse, two processes putatively impaired in patients with schizophrenia, particularly those with formal thought disorder (FTD). We used functional MRI to examine the neural correlates of between-clause and of filled pauses, which are respectively associated with speech planning and speech monitoring. Methods: BOLD contrast was measured while 6 schizophrenia patients with FTD and 6 healthy subjects spoke about Rorshach inkblots. In an event-related design, we examined activity associated with pauses that occurred between clauses and with pauses that were filled. Results: There was no significant group difference in the frequency of between-clause pauses but patients with FTD made strikingly fewer filled pauses than controls. Between-clause pauses were associated with activation in the anterior part of the left superior temporal gyrus (STG) and the left insula in controls and the engagement of these regions was significantly attenuated in patients. Conclusions: The anterior part of the left STG and the left insula are normally involved in both the planning and monitoring of discourse. The attenuated engagement of these regions with between-clause pauses and the striking infrequency of filled pauses in the patients are consistent with cognitive models implicating defective speech planning and speech monitoring in schizophrenia, especially in relation to FTD.